2022
DOI: 10.1002/ep.14012
|View full text |Cite
|
Sign up to set email alerts
|

Gemifloxacin removal from aqueous solution by rice‐straw based activated carbon: Batch adsorption and thermal regeneration

Abstract: Due to the worldwide concern about emerging contaminants in aqueous systems, the main objective of the present study is the adsorption of gemifloxacin (GMF), a fluoroquinolone-type antibiotic, by rice straw-based activated carbon. The rice straw chemically activated with K 2 CO 3 (RSAC) had very high carbon content (>80%) and low silica content (due to the extraction step after activation), high specific surface area (1668 m 2 /g), and oxygenated functional groups. The GMF adsorption capacity of RSAC was relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…14 Examples of modification methods to improve the antibiotic adsorption of rice straw-derived biochar include tannic acid modification, 15 modification with TiO 2 , 16 magnetization method 9 and chemical activation. 17 Chemical activation of rice straw has been used to enhance the adsorption of various adsorbates such metals and dyes; however, limited studies have been reported on antibiotics. 18,19 According to our previous studies, it was found that carbon from rice straw with KOH and H 3 PO 4 activation exhibited high surface area with excellent remediation of methylene blue and Congo red.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Examples of modification methods to improve the antibiotic adsorption of rice straw-derived biochar include tannic acid modification, 15 modification with TiO 2 , 16 magnetization method 9 and chemical activation. 17 Chemical activation of rice straw has been used to enhance the adsorption of various adsorbates such metals and dyes; however, limited studies have been reported on antibiotics. 18,19 According to our previous studies, it was found that carbon from rice straw with KOH and H 3 PO 4 activation exhibited high surface area with excellent remediation of methylene blue and Congo red.…”
Section: Introductionmentioning
confidence: 99%
“…14 Examples of modification methods to improve the antibiotic adsorption of rice straw-derived biochar include tannic acid modification, 15 modification with TiO 2 , 16 magnetization method 9 and chemical activation. 17 Chemical activation of rice straw has been used to enhance the adsorption of various adsorbates such metals and dyes; however, limited studies have been reported on antibiotics. 18,19…”
Section: Introductionmentioning
confidence: 99%